Impact of COVID-19 related national lockdown on care of corneal transplantation patients at a tertiary eye care centre in India - Bhalerao, Sushank Ashok (Indian J Ophthalmol, 2021)
PURPOSE: To study impact of COVID-19 related national lockdown on care of corneal transplantation patients at a tertiary eye centre in Andhra Pradesh state of South India. METHODS: Cross-sectional questionnaire-based study conducted at tertiary eye care centre in Andhra Pradesh state of South India, included 109 patients who underwent keratoplasty(full thickness or partial thickness) at our centre and who came for follow-up visit after lockdown. Factors such as type, indication, number of keratoplasties in the operated eye, and unusual clinical outcomes identified during visit after the lockdown, were studied. Uncorrected visual acuity, best corrected visual acuity, clarity of graft, graft-host junction apposition, intactness of sutures, intraocular pressure and disc status were compared on visits made before and after lockdown. RESULTS: During lockdown, 77.1% patients were properly using medications that was significantly (P = 0.0003) lower than that of before the lockdown (90.8%). After the lockdown, 82.3% patients were using medications properly that was comparable (P = 0.11) to that of during the lockdown (77.1%). The proportion of eyes with clear grafts and intact sutures decreased significantly after lockdown. The unusual outcomes observed after the lockdown were graft failure (36.7%), graft edema (11%), graft infiltrate(5.5%), phthysis bulbi (1.85%) and edematous graft cleared in eyes 3.7% eyes. CONCLUSION: We noted significant drop in usage of medications from 91% before lockdown to 77% during lockdown and maintained at 83% after lockdown. Edematous grafts increased from 41% before lockdown to 54% after the lockdown. Intactness of sutures decreased from 82% before lockdown to 69% after lockdown.